Stratigraphy of the Walk and Post-anthropocentric Narratives: The Case of Antonio Moresco (ENTHYMEMA, 2025)
Drawing on material ecocriticism, new materialism and eco-narratology, this article proposes an analysis of the narrative structure of the novel Gli increati by Antonio Moresco as a case of “Anthropocene storytelling”. Specifically, I consider the practice of walking as a prompt for the novel complex temporal and spatial dimensions. My discussion situates within a broader reflection on the recent challenges posed by the concept of the Anthropocene to traditional modern epistemologies, based on conceptual dichotomies and linearity. I propose that the novel serves as an example of a narrative organised not by the principle of causality, but by what I call “stratigraphic logic”.